Association between polymorphisms in IL21 gene and risk for sepsis. (2nd January 2017) - Miao, Tianyu; Pu, Yan; Zhou, Bin; Chen, Peng; Wang, Yanyun; Song, Yaping; Zhao, Jichun; Zhang, Lin
Abstract: Context: Sepsis is now the leading cause of death in the noncardiovascular intensive care unit (ICU). Objective: To investigate whether polymorphisms in IL21 gene contribute to sepsis susceptibility. Materials and methods: Three single-nucleotide polymorphisms of IL21 (rs907715, rs2055979, rs12508721) were genotyped by TaqMan assay in patients with sepsis and control subjects. Results: Polymorphisms rs2055979 and rs12508721 in IL21 were more frequent in sepsis patients compared to general population. But allele frequency of rs907715 was not significantly different between sepsis patients and control subjects. Conclusion: Polymorphisms in IL21 may be associated with sepsis risk.